Pemasangan Paving Block Jalan Desa Mekar Jaya Kecamatan Panongan Kabupaten Tangerang - Hendro Widiarto; Sukamto; Ika Endrawijaya; Pribadi Asih; Asep Samanhudi (Politeknik Penerbangan Indonesia Curug, 2021)
The road is an important access for residents to do activities, but the village road is still a dirt road, there is no pavement so this will be an obstacle, especially during the rainy season which will complicate community activities. Village roads are something that is really needed by residents, especially for mobility in daily life. The village road is a facility that is really needed by residents in Kp. Blok Benda RT.10 RW. 04 Desa Mekar Jaya Kec. Panongan Tangerang Banten Therefore, the people of Kp Blok Benda Mekar Jaya want the procurement and paving of roads to be carried out immediately along the roads belonging to the Panongan area, especially roads that are considered prone to accidents due to slippery village roads. Seeing the demand from residents who desperately need pavement (concreting or paving) this road. then we carried out the Tri Darma Perguruan Tinggi where the Indonesian Aviation Polytechnic Curug is one of the obligations of lecturers in carrying out community service by taking cases